An Fc-silent OspA monoclonal antibody passively protects mice from tick and intradermal Borrelia burgdorferi challenge - Daniel Palmer; Atieh Shemshadian; Katherine Berman; Ariana Nobles; Graham G. Willsey; Carol Lyn Piazza; Grace Freeman-Gallant; Michael J. Rudolph; Jeff Bourgeois; Linden Hu; David J. Vance; Nicholas J. Mantis (PLoS ONE, 2026)
The monoclonal antibody, LA-2, has played a pivotal role in the development of Outer surface protein A (OspA)-based vaccines for Lyme disease, a multisystem illness caused by the tick-borne spirochete, Borrelia burgdorferi sensu lato. Of particular significance was the demonstration more than three decades ago that LA-2 equivalent antibody titers, defined by a competitive-inhibition ELISA, serve as a reliable correlate of vaccine-induced protection across different species, including humans. In vitro characterization of LA-2 has identified both complement-dependent and -independent activities, although which of these attributes contribute to protection against B. burgdorferi remains unresolved. To address this issue, we generated and characterized an “Fc-silent” version of LA-2 IgG1 carrying so-called LALAPG substitutions (L234A, L235A, P329G). We demonstrate that LA-2 LALAPG retained OspA binding activity but was severely attenuated in in vitro complement deposition and complement-dependent borreliacidal assays. Nonetheless, LA-2 LALAPG was as effective as LA-2 at passively protecting C3H mice against nymphal tick-mediated B. burgdorferi sensu stricto (s.s.) B31 challenge. LA-2 LALAPG was also equivalent to LA-2 in passively protecting BALB/c mice against intradermal B. burgdorferi s.s. B31 challenge. In the intradermal challenge model, viable spirochetes were not recoverable 24 h after injection from skin biopsies of mice treated with LA-2 or LA-2 LALAPG, and an influx of pro-inflammatory cytokines and chemokines to the injection site was abrogated. Collectively, these results suggest that LA-2’s primary mode of action involves direct physical interactions with the spirochete rather than complement-dependent killing. Elucidating these mechanisms may have implications for understanding the mechanistic correlates of OspA-based vaccine-induced immunity in humans.